(3eNJUQ GdeYJeO aiCUhd Gdabgs - (3SdjeGf Hf fGUQ Hf SYjOs; (3eMeO Hf Ydj GdWjH GdHUQj, CHh GdMSjf,J (B436 (3g` s ((3SdjeGf Hf GdeXaQ Hf YjSi Hf eMeO s)
(3ChdgG (B:s
(3GYde Cf GdZQV HPdc gh Gdbhd ai Cf GdELeGY MLI s
(3BNQgG (B:s
(3Ef cd eLJgO eUjH bGd adh cGfhG GLJgOhG eG PcQJe s
(3fSNI KGfjI ecQQI ef Qbe (B129 (3CUhd abgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B275s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs